a)
[tex](3x+4)^2-x(2+9x)=\\\\=(3x)^2+2\cdot3x\cdot4+4^2-2x-9x^2=\\\\=9x^2+24x+16-2x-9x^2=\boxed{22x+16}[/tex]
b)
[tex]2p(3-8p)+(1+4p)^2=\\\\=6p-16p^2+1^2+2\cdot1\cdot4p+(4p)^2=\\\\=6p-16p^2+1+8p+16p^2=\boxed{14p+1}[/tex]
c)
[tex](5a-b)^2+b(10a-b)=\\\\=(5a)^2-2\cdot5a\cdot b+b^2+10ab-b^2=\\\\=25a^2-10ab+b^2+10ab-b^2=\boxed{25a^2}[/tex]
d)
[tex]y(4x+y)-(x+2y)^2=\\\\=4xy+y^2-(x^2-2\cdot x\cdot2y+(2y)^2)\\\\=4xy+y^2-(x^2-4xy+4y^2)=\\\\=4xy+y^2-x^2+4xy-4y^2=\boxed{-x^2-3y^2+8xy}[/tex]
Wykorzystane wzory skróconego mnożenia
[tex](a+b)^2=a^2+2ab+b^2\\\\(a-b)^2=a^2-2ab+b^2[/tex]